A design for a mobile robotic avatar - modular framework - Seet, Gerald Gim Lee (2013)
This paper presents a modular architecture for MAVEN; a mobile robotic avatar. The proposed modular architecture allows for rapid customization to suit changes in application requirements. Aspects of modularity were applied to both hardware and software subsystems in the form of modules for mobility, head and arm gesturing, internet telephony, artificial intelligence (AI) power and communication. Module interconnectivity is achieved using industry standard Ethernet and serial communication standards. This allows modules the flexibility of implementing different operating systems and leveraging on existing development. By grouping hardware and its complementary software into `self-contained' modules, changes in requirements can be implemented with relative ease; configurations can vary from an intelligent information kiosk to an autonomous mobile Avatar, with arms and head units that permit gesturing. The modular approach allows for the reuse of modules, enhancing ease of reconfiguration and cost savings.